PERILAKU HARGA DAN INTEGRASI PASAR BAWANG MERAH DI INDONESIA - Kustiari, Reni (Jurnal Agro Ekonomi, 2017)
EnglishShallot is the main spice widely used in the Indonesian food cooking and servings that makes its demand continues increasing although its price highly fluctuates. This study is intended to analyze price behavior and shallot market integration in Indonesia. This study uses monthly producer and consumer prices data for 2011-2016. The price fluctuation was analyzed with the coefficient of variation. The market integration was analyzed with Johansen's cointegration approach using the Vector Error Correction Model (VECM). The study shows that both producer and consumer prices fluctuations increase after the introduction of Horticultural Product Import Recommendation policy. The Engle-Granger causality test shows that there is no causal relationship between the consumer and producer price of the shallot in Indonesia. The market power and market failure are attributed to the absence of causality. The results of forecast errors variance decomposition analysis indicate that the market in Central Java is the dominant market and can be used as a reference market in predicting the dynamics of consumers? shallot price in Indonesia. Managing shallot production level and amount of shallot supplies in the Central Java markets is the keys for ensuring shallot price stability at national level.IndonesianBawang merah merupakan bumbu masak yang utama bagi masyarakat Indonesia sehingga permintaan bawang merah meningkat terus, walaupun harganya berfluktuasi. Studi ini bertujuan untuk menganalisis perilaku harga dan integrasi pasar bawang merah di Indonesia. Studi ini menggunakan data harga produsen dan harga konsumen bulanan tahun 2011?2016. Fluktuasi harga dianalisis dengan koefisien variasi. Integrasi pasar bawang merah dianalisis dengan pendekatan kointegrasi Johansen menggunakan Vector Error Correction Model (VECM). Penelitian menunjukkan bahwa fluktuasi harga produsen dan harga konsumen meningkat sesudah kebijakan Rekomendasi Impor Produk Hortikultura diberlakukan. Uji kausalitas Engle-Granger menunjukkan bahwa antara harga konsumen dan harga produsen bawang merah di Indonesia tidak terdapat hubungan kausalitas. Hal ini dapat disebabkan oleh adanya market power dan terjadinya kegagalan pasar. Analisis dekomposisi varian kesalahan menunjukkan bahwa pasar Jawa Tengah adalah pasar dominan dan dapat menjadi acuan memprakirakan dinamika harga konsumen bawang merah di Indonesia. Pengelolaan tingkat produksi dan jumlah pasokan bawang merah di pasar Jawa Tengah termasuk sebagai kunci dalam menjaga stabilitas harga bawang merah secara nasional.